Hypoxic changes to the urothelium as a bystander of end-stage bladder disease. Issue 2 (April 2019) - Radford, A.; Hinley, J.; Pilborough, A.; Southgate, J.; Subramaniam, R.
Summary: Introduction: Urothelial cells harvested from benign diseased bladders have a compromised capacity to propagate or differentiate in vitro, potentially limiting their application in autologous tissue engineering approaches. The causative pathways behind this altered phenotype are unknown. The hypothesis is that hypoxic damage to the urothelium occurs as a bystander to chronic or recurrent episodes of infection and inflammation. Objective: The aim of this study was to assess immunohistochemically detected nuclear hypoxia-inducible factor 1 alpha (HIF-1α) and vascular endothelial growth factor in the urothelium when exposed to hypoxia. Study design: Human bladder sections from a total of 29 adult and paediatric patients, representing a variety of different pathologies including neuropathy (n = 15), were analysed. Tissues from adults with bladder outlet obstruction secondary to prostatic disease (n = 1), urothelial carcinoma (n = 1) and tonsil (n = 1) were used as positive tissue controls for immunohistochemistry. Hypoxia-inducible factor 1 alpha–labelled sections were scanned using a Zeiss AxioScan Z1 slide scanner. Analysis of urothelial nuclear HIF-1α labelling was performed using HistoQuest image analysis software (TissueGnostics). Comparison of nuclear HIF-1α labelling between neuropathic and non-neuropathic sections was performed using one-way analysis of variance with the post hoc Tukey honestly significant difference (HSD) test. Patient urodynamic studies performed before tissue sample harvest were evaluated and correlated to the HIF-1α intensity using Spearman's rank correlation. Results: Hypoxia-inducible factor 1 alpha appeared more intense in the urothelial compartment from neuropathic bladder samples ( n = 15) than in the control tissues, including non-obstructed samples ( n = 9). Image analysis supported this; median nuclear HIF-1α labelling was 29.98 ± 3.10 (standard deviation [SD]) ( n = 9) in controls and 74.29 ± 7.55 (SD) in neuropathic samples ( n = 15). A statistically significant difference between the control and neuropathic tissue groups was shown ( P < 0.05 ). Of the 15 neuropathic samples, 11 had traceable urodynamic studies. Both initial and maximum detrusor pressures indicated a positive relationship when plotted against HIF-1α labelling. Spearman's rank correlation, with no missing events, confirmed significant correlations between both initial or maximum detrusor pressure and nuclear HIF-1α labelling intensity (median score); P ≤ 0.046 and P ≤ 0.05, respectively. The null hypothesis was accordingly rejected. Conclusions: This study indicates that urothelial nuclear HIF-1α may be a biomarker of hypoxia and a common feature in end-stage bladder disease associated with high-pressure systems.